2021
DOI: 10.21037/atm-20-3514
|View full text |Cite
|
Sign up to set email alerts
|

Single versus two-stage phalloplasty for transgender female-to-male patients: a systematic review of the literature

Abstract: Phalloplasty is the main treatment for gender dysphoria disorder. It is difficult to ascertain if staging of phalloplasty influences the rate of complications. We aim to describe and compare the rates of complication between single versus two-stage phalloplasty for transgender female-to-male patients. PubMed, Ovid Medline, EMBASE and SCOPUS databases were queried for studies reporting complications of female-to-male transgender patients who underwent phalloplasty. The keywords "phalloplasty", "female to male",… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(88 reference statements)
1
5
0
2
Order By: Relevance
“…These complications were studied by Huayllani et al who demonstrated significantly higher complication rates in two-stage phalloplasties. 18 Similar findings were reported by Remington et al when specifically comparing staging of urethroplasty, where staged procedures had higher rates of flap and urethral complications. 13 Although there is a paucity of evidence to support staging versus no staging in phalloplasty, our results show no significant difference in 30-day complications, including flap failure causing unplanned reoperation, between the two techniques.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These complications were studied by Huayllani et al who demonstrated significantly higher complication rates in two-stage phalloplasties. 18 Similar findings were reported by Remington et al when specifically comparing staging of urethroplasty, where staged procedures had higher rates of flap and urethral complications. 13 Although there is a paucity of evidence to support staging versus no staging in phalloplasty, our results show no significant difference in 30-day complications, including flap failure causing unplanned reoperation, between the two techniques.…”
Section: Discussionsupporting
confidence: 79%
“…16 Multistage procedures have demonstrated poor urethral and flap-related outcomes, with complication rates of 34% and 10% respectively. 17,18 In a large review comparing flap choice in gender-affirming phalloplasty, urethral strictures and fistulas were more common in RFFF, but flap failure rates were higher in This article is protected by copyright. All rights reserved.…”
mentioning
confidence: 99%
“…Vervielfältigung nur mit Zustimmung des Verlages. [77,78]. Die Aussage der Studie wird jedoch durch die Tatsache beschränkt, dass alle nicht tube-in-tube-fähigen Phalloplastiken in die Gruppe der geplanten, mehrschrittigen Urethrakonstruktionen fallen, deren Komplikationsrate durch eine präformierte Urethra mit einem Hauttransplantat ohnehin erhöht erscheint.…”
Section: "Staged" Phalloplastikunclassified
“…Des Weiteren können die verlängerte und die penoidale Urethra, unabhängig von der Art ihrer Konstruktion, sofort oder verzögert anastomosiert werden. Eine Meta-Analyse aus 50 Studien fand eine höhere Komplikationsrate sowie ein schlechteres Outcome (Urinieren im Stehen, Sexualfunktion, Patientenzufriedenheit) bei mehrschrittig durchgeführten Urethroplastiken gegenüber primären Urethraanastomosen [77,78]. Die Aussage der Studie wird jedoch durch die Tatsache beschränkt, dass alle nicht tube-in-tube-fähigen Phalloplastiken in die Gruppe der geplanten, mehrschrittigen Urethrakonstruktionen fallen, deren Komplikationsrate durch eine präformierte Urethra mit einem Hauttransplantat ohnehin erhöht erscheint.…”
Section: "Staged" Phalloplastikunclassified
“…10,11 Recently, the phalloplasty method using the latissimus dorsi flap (LDF) has attracted interest as evidenced by frequent publications and presentations by colleagues from various countries. 12,13 However, the radial forearm free flap and anterolateral thigh flap methods were dominant. The authorship of this method of phalloplasty using an LDF in these publications is not definitely cited and is mainly attributed to Perovic.…”
Section: Introductionmentioning
confidence: 99%